The Cologne Reformation and the Church of Scotland - Cameron, James K. (The journal of ecclesiastical history, 1979)
The apparent suddenness of the reformation in Scotland has sometimes been considered difficult to understand, but more difficul has been the abandonment, seemingly at the eleventh hour, of the old Church by some of those who held key positions in it. The desertion to die reform movement of John Wynram, sub-prior of the St. Andrews Augustinians and dean of die Faculty of Divinity, has recendy called forth this caustic comment from Dr McRoberts, ‘One would very much like to know what religious convictions he really held, if any’. In a footnote McRoberts adds ‘He is reminiscent of his contemporary, Hermann von Wied, archbishop of Cologne, who was described by the Emperor Charles V as “neither a Protestant nor a Catholic but a proper headien’”. The linking of Wynram's name widi rfiat of the archbishop elector, as we shall see, is not widiout foundation, although not necessarily on account of the judgments of the emperor or the monseigneur. No doubt similar comments could be passed on John Douglas, principal of St. Mary's College and rector of die University, who shared widi Wynram, Knox, and odiers in drawing up in 1560 die Scots Confession and the First Book of Discipline.